(untitled) (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
This study aimed to analyze the information related to the studentsâ€™ perspectives on using E-Learning as learning media during the pandemic, which was seen from 2 aspects: perspectives on the advantages and the problems faced. The subject of this study were students in 6 semesters at University of Muhammadiyah Tangerang. This study used descriptive qualitative method. The writers used 3 techniques; interviews, questionnaires, and documentation. The result of this study showed that most of their perspectives of the advantages of using E- learning are; more comfortable and flexible to do anytime and anywhere, saved time, money and transportation costs, upgraded technology and access much information, more safely and independent learning. However, the main problem faced were poor internet signal connection, spent a lot of internet quota. Moreover, there are some students who felt bored, and stressed because of monotonous learning, and lack of knowledge to master the applicationâ€™sÂ Â Â use properly. Â Â